Dissertações e teses da pós-graduação em educação na Unesp-Campus de Marília: um estudo das citações e cocitações (2004 a 2009) - Custódio, Pollyana Ágata Gomes da Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
We assume the assumption according to which the analysis of researchers’ citation and cocitation frequency in certain area help to highlight the authors whose methods, concepts, and theories that underlying their scientific development; as well the core of the relevant literature and the cognitive associations of such area. The research aims at analyzing the most cited and cocited researchers in dissertations and theses in the Teaching, Learning School and Human Development” area of the Post-Graduate Program of Education - Faculty of Sciences of UNESP - Campus of Marilia, during the period of 2004-2009. We analyzed the reference numbers present in 25 dissertations and 23 PhD theses, which were defended between 2004-2009. The data collection was developed by level, Master and PhD. For the 25 dissertations were raised 2082 references and for the 23 theses, 2333 references. For each level we developed a database with the following variables of reference: document type, document language, the reference year of publication, and the authorship of the cited work. These variables allowed us to analyze the most common language, type of documents, the most cited authorship, and the cocitation among the most cited authors. In this context, it was considered as the most cited researchers who received at least six citations. For the analysis of cocitation we built square matrixes for each level, Master and PhD with respective cocitation frequencies among the most cited researchers. To the visualization of the cocitation network we used the Pajek software. The density of cocitation networks was calculated in order to determine the cohesion of cocitation between the cited researchers. The results highlighted 34 most cited authors for the Master, and 29 authors for the PhD. In comparing the Master and the PhD levels, there... (Complete abstract click electronic access below)

Partiu-se do pressuposto que a análise da frequência de citação e cocitação de pesquisadores, em uma área, contribui para evidenciar os autores cujos métodos, conceitos e teorias subsidiam o seu desenvolvimento científico, bem como o núcleo da literatura relevante e as associações cognitivas da área. Foram analisados os pesquisadores mais citados e cocitados nas dissertações e teses defendidas na linha de “Ensino, Aprendizagem Escolar e Desenvolvimento Humano”, do Programa de Pós-Graduação em Educação da Faculdade de Filosofia e Ciências da UNESP/Marília, no período de 2004 a 2009. Como método de pesquisa, foi analisado o conjunto de referências presente nas 25 dissertações de mestrado e 23 teses de doutorado, defendidas entre 2004 a 2009. O levantamento dos dados foi realizado por nível: mestrado e doutorado. Para o total de 25 dissertações, encontraram-se 2082 referências, e para o total de 23 teses encontraram-se 2333 referências. Para cada nível, foi gerado um banco de dados com as seguintes variáveis para cada referência: tipo de documento, idioma do documento, autoria(s) do trabalho citado. A partir destas variáveis, foram analisados o idioma mais frequente, tipologia documental, autores mais citados, cocitação entre os autores mais citados. Neste universo, consideraram-se como pesquisadores mais citados aqueles que receberam pelo menos seis citações. Para a análise de cocitação, foram construídas matrizes simétricas quadradas para cada nível, mestrado e doutorado, com as respectivas frequências de cocitação entre os pesquisadores mais citados. Para a visualização da rede de cocitação, utilizou-se o software Pajek. Foi calculada a densidade das redes de cocitação, a fim de verificar a coesão de cocitação entre os pesquisadores mais citados. Como resultados, destacaram-se...
Keywords: Universidades e faculdades - Pós-graduação - Marília (SP); Educação - Tese; Referencias bibliograficas; Bibliometria; Bibliometrics